Combined association of recipient killer cell immunoglobulin‐like haplotype AA and donor HLA‐C*07 gene with BK virus associated nephropathy in kidney transplant patients. (19th December 2019) - Kovacevic Vojtusek, Ivana; Burek Kamenaric, Marija; Ivkovic, Vanja; Bulimbasic, Stela; Marekovic, Ivana; Coric, Marijana; Bosnjak, Zrinka; Grubic, Zorana; Zunec, Renata
Abstract : Kidney transplant recipient killer cell immunoglobulin‐like receptors (KIR) genotype and HLA‐C status of their donors have been separately associated with BK virus‐associated nephropathy (BKVAN) and BK virus infection. Our aim was to determine whether different combinations of recipients KIR genes and donor HLA‐C ligands influence the risk of BKVAN. Retrospective case‐control study included 23 recipients with BKVAN and 46 recipients with persistently negative BK virus. Donor HLA‐C*07 positivity was associated with lower odds for BKVAN, recipients bearing KIR haplotype AA or lacking any activating KIR genes were more frequent in BKVAN while recipient/donor combination HLA‐C*07 negative/KIR AA positive was significantly associated with BKVAN. Our study complements and confirms results from several previously published studies, suggesting potential clinical usefulness.